Productivity and composition of microalgae in fish tank in different Malaysian weather conditions - Sahab, Hayfaa Mohammed (2018)
Climate change is affecting every country all over the world such as Malaysia. Climate change is the result of global warming which causes changes in daily weather conditions and water bodies. Many scientists study the water quality and microalgae separately from influence of weather conditions. However, there are few researches about effect of different stocking density of fish under different weather conditions on water quality parameters, mixed microalgae species composition, diversity, productivity, biochemical composition, and toxicity of mixed microalgae. Therefore, the objectives of this study was to see effects of changing weather conditions on water quality, diversity and succession of microalgae, primary productivity, biochemical composition, and toxicity of mixed microalgae in different stocking density of fish (Control (no fish),10, 20, 40, and 80 fish). The weather conditions were monitored three times daily in the morning (8.00-9.00), noon (12.00-13.00), and afternoon (16.00-17.00). The weather is categorized into mix, wet, and dry conditions based on weather scoring. The sampling of five tanks were done every two days and performed outdoor; it’s carried out for water quality, microalgae species and diversity, microalgae biomass, productivity, biochemical composition, and toxicity of mixed microalgae. Statistical analysis were done using one way ANOVA, Factorial ANOVA for microalgae parameters, and XLSTAT for toxicity test of microalgae. The mean of water quality parameters of the five tanks during all weather conditions were: water temperature (27.71, 27.83, 27.77, 27.79, 27.96 °C), pH (7.25, 7.03, 7.05, 6.96, 7.04), electrical conductivity (0.15, 0.15, 0.15, 016, 0.16 mS/cm), total dissolved soilds (0.09, 0.09, 0.09, 0.09, 0.10 mg/L), dissolved oxygen (5.44, 5.31, 5.1, 4.62, 4.13 mg/L), salinity (0.06, 0.06, 0.06, 0.07, 0.07 ppt), secchi disk depth (0.40, 0.17, 0.19, 0.20, 0.22 m), nitrate-nitrogen (0.93, 0.21, 0.21, 0.23, 0.21mg/L), orthophosphates (0.03, 0.14, 0.14, 0.16, 0.15 mg/L), ammonium-nitrogen (0.012, 0.045, 0.046, 0.048, 0.053 mg/L), alkalinity (41.89, 47.70, 46.76, 44.17, 48.17 mg CaCO3/L), total nitrogen (0.23, 0.16, 0.16, 0.17, 0.17 mg/L), total phosphorus (0.008, 0.049, 0.046, 0.049, 0.048 mg/L), TN: TP (32.72, 3.46, 3.45, 3.39, 3.52) respectively. A total of 55 species belonging to 6 divisions (Chlorophyta, Cyanophyta, Chrysophyta, Dinophyta, Bacillariophyta, and Euglenophyta) have been collected from 5 tanks in different weather conditions. The division Chlorophyta was the most dominant in five tanks within different weather conditions comprising of 62.2, 80.3, 81.3, 78.3, and 84.3% in control, tanks 1(10 fish), 2 (20 fish), 3 (40 fish), and 4 (80 fish) respectively. The density of microalgae was high in dry weather conditions but was low in wet weather. The total number of species of microalgae in wet and mix weather conditions were higher than number of species in dry weather conditions. Tank 4 (80 fish) showed the highest chlorophyll concentration of 11.51 μg/L followed by tanks 3, 2, 1, and control [(40, 2, 10 fish) and control (no fish)] 10.75, 9.38, 8.71, and 2, 56 μg/L respectively. The primary productivity was high in tank 4 with high stocking density of fish in dry weather conditions. For biochemical components, the protein contents were high in tanks 4, 3, 2, 1 (49.69, 46.35, 42.82, and 37.55 %) respectively, while the lipid and carbohydrate showed fluctuation rates with (6.83, 8.93, 3.04, 1.78 %), (8.50, 4.55, 1.91, and 2. 77%) in tanks (1, 2, 3, and 4) respectively. The percentage of brine shrimp mortality was 70% in concentration 1000 μg/mL in dry weather conditions, while the lowest percentage was 10% in 1 μg/Ml in wet weather conditions. The average response of Artemia sp. mortality rate against variable dose of extracted mixed microalgae was 538.90, 1256.21, 1444.66, 1222.00 and 1254.13 mg/L in tanks (control, 1, 2, 3, and 4). The environmental factors such as temperature and light intensity were the main factors that increased the primary productivity of microalgae, whereas the reduction of light intensity in mix and wet weather due to cloud covers led to decrease in microalgae primary productivity. The conclusion of this study demonstrates that temperature and light intensity have impacted the water quality parameters, microalgal diversity and productivity. Typically, the mixed microalgae grown in the fish tank were not toxic for brine shrimp. The relationship between different stocking density of fish and different weather conditions have influenced on the water quality and microalgae growth.